RENCANA AKSI PENERAPAN STANDAR PELAYANAN MINIMAL SEBAGAI RESPON PERMASALAHAN PENYELENGGARAAN BIDANG PEKERJAAN UMUM PROVINSI BANTEN - Arlan Marzan; Isvan Taufik; Karvina Budiwati Apriliani; Resti Meliana Sari (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
Minimum standards of service (Standar Pelayanan Minimal/SPM) is provisions regarding the type and quality of basic services which are government affairs that must be provided to every citizen at a minimum. The minimum standards for the public works sector consist of the implementation of drinking water supply systems (SPAM) and the implementation of domestic waste water supply systems (SPALD). Challenges in achieving SPM targets in Banten Province include limited infrastructure, availability of water resources, and sanitation problems that are still faced by most regions. This research aims to outline the action plan for implementing SPM in Banten Province as a response to the problems of implementing SPM in the public works sector and as part of the regional government's efforts to improve the quality of public services. This research was studied using a qualitative descriptive approach. The results of the research show that the SPM action plan in the field of public works to respond to problems in Banten Province includes: Synchronizing regional targets with national policies, this synchronization aims to share affairs and budgeting as well as joint goals that have been prepared, funding and development of SPAM and SPALD in strategic areas provinces in order to help districts/cities improve access to services and quality of SPM. With this action plan, it can clear up the roadmap for implementing SPM in the field of public works so that it is possible to get support from the central government, innovate financing strategies, increase opportunities for private sector participation, so that Banten Province has a great opportunity to achieve the SPM target in 2030 in accordance with the national vision and regional